Role of pharmaco-epidemiology in psychopharmacology: a study in psychiatric out-patient department of a tertiary care teaching hospital at Dehradun, Uttarakhand - Dutta, Shaktibala; Beg, Mirza Atif; Sindhu, Saubhagya; Singh, Nand Kishore (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Prescription auditing studies are a part of drug utilization studies, are beneficial in clinical practice for rational prescribing of drugs and helpful for minimizing the medication errors. They are important tool to promote rational prescribing. Methods: This wasa prospective drug utilization study conducted by the Department of Pharmacology in Psychiatry out-patient department at Shri Guru Ram Rai Institute of Medical and Health Sciences, Dehradun for a period of 6 months. A total of 311 prescriptions were evaluated for prescribing pattern using World Health Organization drug indicators and National Essential Medicine List (NEML) 2011. Results: A total of 311 prescriptions were evaluated, 157 (50.48%) were females, and 154 (49.52%) were males, mean age was 37.14±0.8 years. Majority of patients were married 207 (66.56%), housewife 116 (37.30%) and belong to middle socioeconomic group 205 (65.92%). A total of 1250 drugs were prescribed, anti-anxiety (anti-A) 379 (30.32%), anti-depressants (anti-Ds) 348 (27.84%), anti-psychotics (anti-Ps) 118 (9.44%), anti-epileptics (anti-Es) 64 (5.12%), mood stabilizer 20 (1.6%), anti-cholinergics 28 (2.24%) and others 293 (23.44%). Oral formulations 1247 (99.76%), 4.02 drugs/prescription, 100% drugs were prescribed by brand names. 220 (17.6%) fixed dose combinations were prescribed. Most frequently prescribed among anti-A drugs were propranolol 160 (42.22%) and diazepam 105 (27.70%), among anti-Ds drugs were amitriptyline 65 (18.68%) and escitalopram 59 (16.95%) and among anti-Ps risperidone 49 (41.53%) and olanzapine 38 (32.20%), respectively. About 51.36% drugs were prescribed from the NEML 2011. Result has revealed polypharmacy in the practice. Conclusions: Anti-A drugs were the most commonly prescribed drugs followed by anti-Ds, anti-Ps and anti-Es respectively. Rational prescribing requires further consideration with special reference to polypharmacy and providing feedback to the physicians.